KAZNA DOŽIVOTNOG ZATVORA U EVROPSKOM SISTEMU ZA ZAŠTITU LJUDSKIH PRAVA - Nezir Pivić; Lejla Zilić-Čurić (Revija za kriminologiju i krivično pravo)
Sentencing to life imprisonment is not in contrast with human rights issued in European Convention for the protection of Human Rights and Fundamental Freedoms. However, the sentenced imposed to life imprisonment and system to of its execution must meet certain standards to be compatible with requirements stated in Article 3 of European Convention. The subject of our research paper are mentioned standards that Contracting States have to respect in terms of enforcing the sentence of life imprisonment. Introduction to the subject of the research is given in the form of penological review of life imprisonment as well as review of internationally established legal standards under the umbrella of the United Nations and the Council of Europe that relate to sentencing and enforcement of life imprisonment. In focus of this research paper is case law of the European Court of Human Rights that refer to life imprisonment. In that context, the focus of this research paper deals with the issue of the relationship between life imprisonment and prohibition of torture as human right that is absolutely protected and the issue of the Contracting States’s margin in appreciation in prescribing the form and conditions of revision of the sentence. The intention of the authors is focused on the legal analysis of Strasbourg case law on issue of compatibility of life imprisonment with the requirements of the Article 3 of the European Convention and to present the standards generated by Strasbourg case law regarding the implementation and mechanism of revision of life imprisonment.